Organizing Medical Care to Patients with Severe Pneumonias in the Presence of A/H1N1 Influenza - K. G. Shapovalov; T. Ye. Belokrinitskaya; V. F. Liga; N. V. Lareva; A. P. Filev; Yu. V. Parkhomenko; F. R. Cheptsov; V. A. Shilnikov; I. N. Shilina; S. V. Kostromitin; A. R. Makhazagdayev; D. N. Shishenkov; et al. (Общая реаниматология)
The paper describes the way medical and intensive cares are organized to patients with complicated forms of A/H1N1 and seasonal influenzas in the Trans-Baikal Territory in the fall of 2009.